2016
DOI: 10.1002/msc.1139
|View full text |Cite
|
Sign up to set email alerts
|

‘It is a Big Thing’: Exploring the Impact of Osteoarthritis from the Perspective of Adults Caring for Parents – The Sandwich Generation

Abstract: Purpose. The aim of the present study was to explore the experiences and impact of caring for an individual with severe osteoarthritis (OA) from the perspective of adult children, looking at the relationship between adult children caring for parents with this condition and the tensions of the 'sandwich generation'. Methods. A mixed qualitative approach, combining focus groups and individual semi-structured interviews was used. In total, 36 participants were purposively sampled and discussed the impact of carin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These daughters described caregiving as a lonely experience and identified situations in which there was a complete lack of support, especially from male siblings. The resentment towards siblings who are dismissive and who do not contribute to their expected share of responsibilities can increase the erosion of family relationships (Barker et al, 2017; Lashewicz, 2014). To date, most studies have focused on the experiences of the marital dyad, showing that haemodialysis demands can disrupt the couple's relational dynamic (Moore et al, 2020; Sousa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These daughters described caregiving as a lonely experience and identified situations in which there was a complete lack of support, especially from male siblings. The resentment towards siblings who are dismissive and who do not contribute to their expected share of responsibilities can increase the erosion of family relationships (Barker et al, 2017; Lashewicz, 2014). To date, most studies have focused on the experiences of the marital dyad, showing that haemodialysis demands can disrupt the couple's relational dynamic (Moore et al, 2020; Sousa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…1). All carers described the physical and emotional toll of caring, similar to that seen in carers of parents with OA [23], in which three themes emerged: the physical and emotional work of caring, changes in family roles and the inequity of caring within the family. A study of family caregivers for patients with RA/AS found that the primary consequences were loss of purchasing power, work problems, social isolation and emotional stress [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, middle-aged women in the sandwich generation engage in less exercise and have fewer health checkups, and women with multiple roles generally have worse health [ 12 ]. International studies have reported that people with dual caring responsibilities experience imbalances in caregiving roles within the family [ 13 ] and feel stressed about balancing caring for their parents and their other roles [ 14 ]. Women who care for both children and older people report a higher rate of subjective feelings of ill health [ 15 ].…”
Section: Introductionmentioning
confidence: 99%